Regular patterns of play in effectiveness offensive sequences of FC Barcelona counterattack - Sarmento, H.; Barbosa, A.; Martins, J.; Campanico, J.; Anguera, M. T.; Leitao, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
While the results of the literature suggest that the increase in transitions (from defense to offence) speed is linked with an increased likelihood of scoring a goal, very few studies have analyzed the transition as a whole. Thus, the aim of the present study is to demonstrate the potential of the software THÈME 5.0, for the detection of behavior temporal patterns (T-pattern) in the football game, more specifically, in the actions of counterattack of the FC Barcelona, accessing to the interaction contexts in which the behaviors are performed. The sample consisted of 12 football games of domestic competitions that were analyzed by systematic observation by using a specific instrument to observe the offensive process (Sarmento et al., 2010). We used the software THÈME 5.0., and the following criteria were used: the minimum number of events was set at 3 and the level of significance was set at 0.05. The analysis revealed the existence of 787 different T-patterns in the sequences of the counter-attack. The study of these patterns allowed the knowledge of specific regularities in the offensive sequences of this team, particularly regarding the understanding of how these start, develop and end. This analysis helps us to characterize the transitions (defense-attack) that are associated with total effectiveness (goal scored) in this team. In general, in this type of sequences, the recovery of the ball possession is performed through a interception of the ball in zone 6 of the field, in a interaction context characterized by the numerical superiority; then we observe a quick change in the flank of play (right side to the left side), where a player progresses in the field performing short passes and conductions of the ball in situations of numerical equality. These sequences ended in the central zone (zone 11) of the offensive sector, through a shot with goal scored in an interaction context of numerical inferiority. This type of analysis allows us to know and to characterize the regular structures of offensive sequences in football teams. The t-patterns detected in the defense-attack transition of this successful team allowed us to know how that process is developed in an effective way. This information is relevant, on the one hand to the team itself because it makes it possible to conceive training exercises in order to increase this efficiency, on that other hand it allows, for example, that the opposing coaches can develop strategies to prevent that the Barcelona team performed these transitions effectively.